Primary hepatic perivascular epithelioid cell tumor: A case report and review of literature - Komson Wannasai; Puwitch Charoenchue; Worakitti Lapisatepun; Tarathep Wongsuriyathai; Sarawut Kongkarnka (Elsevier, 2023)
Primary hepatic perivascular epithelioid cell tumors (PEComas) are extremely rare soft-tissue tumors with few published reports. Herein, a case of a primary hepatic PEComa is reported, along with a review of relevant literature. A mass in the right lobe of the liver was observed during the treatment of a 24-year-old Thai woman with systemic lupus erythematosus. Imaging studies detected a liver mass in segments seven and eight. The patient underwent a right hepatectomy. A tan-brown expansile mass with well-defined borders measuring 3.5 × 4 × 3.3 cm was identified. The tumor consisted of atypical epithelioid cells arranged in a diffuse growth pattern. Thick-walled blood vessels, smooth muscle cells, myxohyaline stroma, and adipose tissue were not observed. HMB45, CD31, and actin were diffusely immunoreactive in the tumor cells, whereas CD117, S100, and hepatocyte-specific-antigen were not. Follow-up revealed recurrent hepatic tumors. This case has been described owing to the rarity of the tumor and the useful correlation between radiologic and pathological findings.